2000
DOI: 10.1055/s-2000-8544
|View full text |Cite
|
Sign up to set email alerts
|

A New Acylated Flavonol Glycoside and Antioxidant Effects of Hedyotis diffusa

Abstract: A study on the bioactive principles of Hedyotis diffusa Willd., led to the isolation of a new acyl flavonol di-glycoside which was characterized as kaempferol 3-O[2"-O-(E-6'"-O-feruloyl)-beta-D-glucopyranosyl]-beta-D-galactop yranoside by spectral and chemical methods from the methanolic extract. In addition, three known flavonol glycosides and six known iridoid glycosides were also obtained. The above-mentioned glycosides were tested for antioxidant effects on xanthine oxidase inhibition, xanthine-xanthine ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 7 publications
3
41
0
Order By: Relevance
“…[33] The extract protected renal tissues, significantly suppressed the production of TNF-α, IL-1, IL-6 and MCP-1, as well as significantly promoted the production of IL-10 in serum and renal tissues.…”
Section: Antioxidant Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] The extract protected renal tissues, significantly suppressed the production of TNF-α, IL-1, IL-6 and MCP-1, as well as significantly promoted the production of IL-10 in serum and renal tissues.…”
Section: Antioxidant Effectsmentioning
confidence: 99%
“…Iridoids are one of the most important components in H. diffusa with various bioactivities, such as anti-oxidant, neuroprotective and anti-inflammatory effects [33,53]. Accompanied with the analysis of the NMR spectra of the pure compounds, the methods of tandem mass spectrometry (MS n ) and time-of-flight mass spectrometry (TOF/MS) have become more popular for the identification of these compounds [11,14,15,25,52].…”
Section: Iridoids and Triterpenesmentioning
confidence: 99%
“…12,13) Our results showed that inhibition of malondialdehyde (MDA) formation increases with increasing concentrations of test compounds and trolox. The peracylates 2a and 2b also showed notable inhibitory effects with IC 50 values 21.81 and 13.59 mg/ml, respectively.…”
Section: Resultsmentioning
confidence: 85%
“…1 H-NMR (400 MHz) and 13 C-NMR (100 MHz) spectra were recorded on a Varian Mercury-400 (400 MHz; Varian Inc., CA, U.S.A.) spectrometer whereas the EI-MS was taken on a TurboMass mass spectrometer and FAB-MS on a JMS-HX 110 mass spectrometer (Perkin Elmer Inc., MA, U.S.A.). Optical specific rotation was measured by Jasco model DIP-370 Digital Polarimeter (JASCO Inc, MD, U.S.A.).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, it was found that many Taiwanese folk herbs have pharmacological functions such as anti-inflammation, anti-virus, anti-cancer, immune enhancement, antioxidant, anti-aggregation and hepatoprotection (Chang et al, 2005;Hsu et al, 2005;Kuo et al, 2004;Lin et al, 2000Lin et al, , 2002Lin et al, , 2007Lu et al, 2000;Wu et al, 2004;Yang et al, 2005Yang et al, , 2007Yen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%